Higher HEI-2015 scores are associated with lower risk of gout and hyperuricemia: Results from the national health and nutrition examination survey 2007–2016 - Nie, Jiaqi; Deng, Ming-Gang; Wang, Kai; Liu, Fang; Xu, Haoling; Feng, Qianqian; Li, Xiaosong; Yang, Yichi; Zhang, Ruyi; Wang, Suqing (Frontiers in Nutrition, 2022)
Gout is the most common inflammatory arthritis with an increasing prevalence in the US and worldwide, which seriously affects people’s quality of life and harms their health. Few studies have focused on the relationship between daily dietary quality and gout, so the topic requires further exploration. Data was derived from National Health and Nutrition Examination Survey 2007–2016 and the inclusion criteria of the analytic sample were: (1) adults, age ≥ 20, with complete information about HEI-2015, gout, and uric acid; (2) complete information of demographics, lifestyle (BMI, smoking, drinking), disease history (hypertension, chronic kidney disease, diabetes). The Healthy Eating Index 2015 (HEI-2015) was used to reflect the quality of the daily diet. The Scott–Rao chi-square tests were used to test the baseline characteristics of different groups. Weighted logistic regression models were used to explore the relationship between the HEI-2015 score and gout/hyperuricemia (HUA) risk. Weighted quantile sum (WQS) regression models were used to assess the contributions of various dietary components in HEI-2015 to reducing gout/HUA risk. After adjusting for demographic characteristics, behavioral covariates, and disease history, higher HEI-2015 scores were associated with a significantly lower risk of gout (OR: 0.878, 95% CI: 0.876-0.880) and HUA (OR: 0.978, 95% CI: 0.976-0.979) in weighted logistic regression. Dairy, Whole Grains, Plant Proteins, and Added sugar contributed greatly in HEI-2015 to reducing gout risk (weights of WQS index: 42%, 17.18%, 16.13%, and 7.93%, respectively). Dairy, Total Fruits, Greens and Beans, and Plant Proteins contributed greatly in HEI-2015 to reducing HUA risk (weights of WQS index: 28.9%, 17.13%, 16.84%, and 11.39%, respectively). Therefore, adherence to the dietary guidelines for Americans may help to reduce the risk of gout/HUA in U.S. adults and more attention should be paid to dairy products, whole grains, fruits, legumes, and added sugars.